Izin Poligami di Pengadilan Agama: (Studi Kasus Putusan PA Samarinda Nomor 2007/Pdt.G/2024/PA.Smd) - Suci Nurhidayah; Siti Saadah; Verdiana Dwi Erlyna; Syahrul Adam (Indo Publishing, 2026)
This article discusses the implementation of polygamy permits in the Samarinda Religious Court, using a case study of Decision Number 2007/Pdt.G./2024/PA.Smd. Polygamy in Islam is permitted under certain conditions, as long as the husband is able to act fairly, has financial means, and obtains permission from the first wife. This research uses a qualitative, normative method with a library study approach to examine the legal basis, procedures, and judges' considerations in granting permission for polygamy. The results show that the judge in the case granted the applicant's request for permission for polygamy because the legal requirements, both alternative and cumulative, were met, as stipulated in Law Number 1 of 1974 and the Compilation of Islamic Law (KHI). This decision reflects that permission for polygamy is not granted freely, but rather through legal, moral, and social considerations to safeguard the family's well-being and protect the rights of the wife and children.